Implementation of Access and Benefit Sharing in Indonesia: Review and Case Studies - Ani Mardiastuti (Jurnal Manajemen Hutan Tropika, 2019)
The Nagoya Protocol on Access and Benefit-Sharing (ABS) was adopted in 2010, but Parties have been facing many challenges to implement the Protocol.   The objective of this paper is to provide information on the current status of the ABS implementation in Indonesia, and to present some case studies for drawing the lessons learned.  Information was collected through desk study and a Focal Group Discussion involving 25 resource persons from various stakeholders.  There were many institutions related to ABS, but unfortunately some key functions for ABS were still not assigned to a specific institution(s).  For law and regulations, there was no law and regulations specifically created for ABS (except Law no. 11/2013 on the Ratification of the Nagoya Protocol), but many existing laws and regulations can be used to address various issues related to ABS.  From three case studies presented, it was clear that there were many constraints and challenges to implement the Protocol.  The institutional arrangement as well as law and regulations are very crucial to ensure a fair and equitable sharing of the benefits derived from the use of genetic resources, under Nagoya Protocol.